THE MEDIATING ROLE OF HOPE IN THE ASSOCIATION BETWEEN RESILIENCE AND PSYCHOLOGICAL DISTRESS AMONG CLINICAL CLERKSHIP STUDENTS - Zulfadli Akbar Amir; Dina Vebiana; Rizki Indriana Wulan Savitri; Putu Divariani; Rahma Dona; Amalia Rosyida; Arina Salsabiela (Universitas Muhammadiyah Lampung, 2026)
Medical students undertaking clinical clerkships face substantial academic, clinical, and emotional demands that may increase their vulnerability to psychological distress. This study examined whether hope statistically mediated the association between resilience and psychological distress among clinical clerkship students. Using a cross-sectional correlational design, 188 participants were recruited through nonprobability voluntary-response sampling. Data were analyzed using an observed-variable path model in JASP Version 0.16.4. The results indicated that hope fully mediates the relationship between resilience and psychological distress. Resilience was positively associated with hope (β = .781, p < .001), while hope was negatively associated with psychological distress after controlling for resilience (β = −.681, p < .001). The component regression models indicated that resilience explained 61.0% of the variance in hope (R² = .610), whereas resilience and hope jointly explained 38.8% of the variance in psychological distress (R² = .388). The standardized indirect effect of resilience on psychological distress through hope was significant (β = −.532, p < .001). After including hope in the model, the direct relationship between resilience and psychological distress was not significant (β = .076, p = .492). These findings support the hypothesized indirect relationship through hope. Given the cross-sectional design, the results should be interpreted as a statistically indirect association rather than evidence of temporal or causal mediation processes. Overall, the findings highlight the relevance of hope in efforts to promote psychological well-being among medical students.